The Power of Strategic Listening - Lewis, Laurie (Rowman & Littlefield Publishers, 2019)
Is Your Organization Designed to Listen demonstrates that listening is an invaluable tool for strategic action that is essential to the success of contemporary organizations. Lewis gives organizations the tools to assess and improve their techniques for listening, including development of how they process and respond to what is heard.